In its active form, the GTP-binding protein rab8 interacts with a stress-activated protein kinase. - Ren, M (1996)
Rab8 is a small GTP-binding protein that plays a role in vesicular transport from the trans-Golgi network to the basolateral plasma membrane in polarized epithelial cells (MDCK), and to the dendritic surface in hippocampal neurons. As is the case for most other rab proteins, the precise molecular interactions by which rab8 carries out its function remain to be elucidated. Here we report the identification and the complete cDNA-derived amino acid sequence of a murine rab8-interacting protein (rab8ip) that specifically interacts with rab8 in a GTP-dependent manner. Rab8ip displays 93% identity with the GC kinase, a serine/threonine protein kinase recently identified in human lymphoid tissue that is activated in the stress response. Like the GC kinase, rab8ip has protein kinase activity manifested by autophosphorylation and phosphorylation of the classical serine/threonine protein kinase substrates, myelin basic protein and casein. When coexpressed in transfected 293T cells, rab8 and the rab8ip/GC kinase formed a complex that could be recovered by immunoprecipitation with antibodies to rab8. Cell fractionation and immunofluorescence analyses indicate that in MDCK cells endogenous rab8ip is present both in the cytosol and as a peripheral membrane protein concentrated in the Golgi region and basolateral plasma membrane domains, sites where rab8 itself is also located. In light of recent evidence that rab proteins may act by promoting the stabilization of SNARE complexes, the specific GTP-dependent association of rab8 with the rab8ip/GC kinase raises the possibility that rab-regulated protein phosphorylation is important for vesicle targeting or fusion. Moreover, the rab8ip/GC kinase may serve to modulate secretion in response to stress stimuli.